IMPLEMENTASI PROGRAM KEMITRAAN DI PT. JASA RAHARJA (PERSERO) CABANG RIAU - Aulia, Feren; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The Partnership Program is one of CSR (Corporate Social Responsibility) implemented by PT. Jasa Raharja (Persero) Branch of Riau as one of the state-owned companies (BUMN). The Partnership Program is a program to increase the ability of small business activities to become tough and independent through the use of funds from corporate profits. Partnership Program at PT. Jasa Raharja (Persero) is implemented based on the desicion of the minister state-owned companies Number: PER-09/MBU/07/2015 about Partnership and Community Development Programs. The purpose of this study was to know the implementation of the partnership program at PT. Jasa Raharja (Persero) Branch of Riau and whats factor that inhibit the implementation. The concept oh the theory is theory of Policy Implementasion by Van Meter Van Horn (Agustino, 2016) i.e. The method of this research is use qualitative method with phenomenological approach and data collection technique done with interview, observasion, and documentation. The results of this study indicate that the implementation of the partnership program at PT. Jasa Raharja (Persero) Branch of Riau runs smoothly, there are six indicators that determine the success of a policy according to Van Meter Van Horn including: standard and policy objectives; resource; communication between organizations and strengthening activities; implementing agent characteristics; economic, social and political conditions and the disposition of the implementor. Â Keywords: Implmentation, Program, Partnership